مدى اعتماد المستثمرين على التحليل المالي في سوق دمشق للأوراق المالية دراسة مسحية من وجهة نظر عينة الدراسة - إسماعيل, إسماعيل; سوسق, أيمن (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يهدف البحث إلى دراسة مدى اعتماد المستثمرين في سوق دمشق للأوراق على التحليل الأساس والتحليل الفني في اتخاذ القرارات الاستثمارية, ودراسة العوامل المؤثرة على مدى اعتماد المستثمرين على التحليل الأساسي والتحليل الفني في اتخاذ قراراتهم . وتناول البحث في جانبه النظري مفهوم التحليل الأساس عبر تعريفه وأهميته، ومصادر معلوماته، ومعاييره، والطرق والأساليب المستخدمة فيه, والتحليل الفني وأدواته لسعر السهم والسوق ونظريات وتحليلات متقدمة في التحليل الفني. و لتحقيق أهداف واختبار فرضيات البحث تم جمع البيانات من خلال دراسة مسحية باستخدام الاستبانة كأداة لجمع البيانات على عينة من المستثمرين في سوق دمشق للأوراق المالية, والعاملين في شركات السمسرة والوساطة المالية ( نظراً لتلقيهم أوامر البيع والشراء من المستثمرين مباشرة سواء عن طريق الاتصال المباشر الشخصي أم عن طريق الاتصال غير المباشر, ومن ثم معرفة الوسطاء والسماسرة ردود فعل المستثمرين والأسس التي اعتمد عليها المستثمرون في اتخاذ قراراتهم), والاستشاريون في الشركات والمكاتب التي تقدم الخدمات والاستشارات المالية ( نظراً لأقدام العديد من المستثمرين إلى تلك الشركات والمكاتب للاستفادة من خبراتهم , ومن ثم قدرة الاستشاريين على معرفة ردود فعل المستثمرين وتقويم الأسس التي اعتمد عليها المستثمرين في اتخاذ قراراتهم ) . واهم ما خلصت إليه الدراسة من نتائج : الاعتماد على التحليل الأساسي بشكل كبير والاعتماد على التحليل الفني بشكل ثانوي, و ضعف الثقة بنتائج التحليل الفني والثقة بدرجة اكبر في نتائج التحليل الأساس . لا يمتلك المستثمرون الوعي الكافي والمعرفة الكافية بأدوات وأساليب التحليل الأساس و التحليل الفني مما يؤثر سلباً على اعتمادهم على التحليل الأساسي و التحليل الفني في اتخاذ قراراتهم. تؤثر الإشاعات السائدة في السوق والأخبار المنشورة في وسائل الأعلام ونصائح الأصدقاء وقلة الشركات المدرجة وقلة حجم التداول في سوق دمشق بشكل سلبي على الاعتماد على التحليل الأساسي والتحليل الفني في اتخاذ القرار الاستثماري. The research aims to study the extent of reliance by the investors in DSE on fundamental analysis and technical analysis in making investment decisions, additionally examines factors affecting the extent of reliance of investors on those techniques in their decision-making. The research in theoretical part concept of fundamental analysis by displaying the definition , importance , information sources , standards , methods and techniques used in fundamental analysis and technical analysis by displaying the tools for the stock price and market theories and analyzes of advanced technical analysis. To achieve the objectives of the research hypotheses and test the hypotheses , data was collected through a survey using a questionnaire as a tool to collect data on a sample of investors in the market Damascus Securities Exchange, and working in the brokerage companies and financial intermediation (Because of the receiving buy and sell orders from investors directly, either through direct personal contact or through indirect contact, and therefore knowledge intermediaries and brokers reactions of investors and the foundation upon which investors make their decisions), and consultants in companies and offices that provide services and financial advisory (Because of the feet of many investors to these companies and offices to benefit from their expertise, and therefore the ability of consultants to find out the feedback of investors and evaluate the foundations relied upon by investors in making their decisions).The most important conclusions of the study results: 1. Reliance on fundamental analysis largely and dependence on technical analysis secondarily, and the lack of confidence the results of the technical analysis and trust more in the results of fundamental analysis. 3 . Investors did not have enough awareness and enough knowledge tools and methods of fundamental analysis and technical analysis, which negatively affects their dependence on fundamental analysis and technical analysis in making their decisions. 4 . Affect rumors prevailing in the market and the news published in the media and friends tips and a few listed companies and the lack of trading volume in the market Damascus passively rely on fundamental analysis and technical analysis in the investment decision.